Microparticle Release During Normal Cesarean Delivery. Issue 3 (September 2018) - Hofer, J.E.; Scavone, B.M.
Abstract : ( Anesth Analg . 2018;126:925–927) Microparticles (MPs) are spherical cytoplasm-free parts of cell membranes released from cells during physiological or pathologic processes; the origin of MPs can be identified based on their membrane proteins. The relationship between coagulability and MP levels surrounding normal delivery has not been characterized. A better understanding of peripartum coagulation may permit better identification of those at risk for postpartum hemorrhage. The authors of this brief report hypothesized that an increase in MP levels in plasma occurs around the time of placental separation and subsides after several hours.